Does stapedotomy improve high frequency conductive hearing?. Issue 4 (11th June 2021) - Roychowdhury, Prithwijit; Polanik, Marc D.; Kempfle, Judith S.; Castillo‐Bustamante, Melissa; Fikucki, Cheryl; Wang, Michael J.; Kozin, Elliott D.; Remenschneider, Aaron K.
Abstract: Objectives: Stapedotomy is performed to address conductive hearing deficits. While hearing thresholds reliably improve at low frequencies (LF), conductive outcomes at high frequencies (HF) are less reliable and have not been well described. Herein, we evaluate post‐operative HF air‐bone gap (ABG) changes and measure HF air conduction (AC) thresholds changes as a function of frequency. Methods: Retrospective review of patients who underwent primary stapedotomy with incus wire piston prosthesis between January 2016 and May 2020. Pre‐ and postoperative audiograms were evaluated. LF ABG was calculated as the mean ABG of thresholds at 250, 500, and 1000 Hz. HF ABG was calculated at 4 kHz. Results: Forty‐six cases met criteria. Mean age at surgery was 54.0 ± 11.7 years. The LF mean preoperative ABG was 36.9 ± 11.0 dB and postoperatively this significantly reduced to 9.35 ± 6.76 dB, ( P < .001). The HF mean preoperative ABG was 31.1 ± 14.4 dB and postoperatively, this also significantly reduced to 14.5 ± 12.3 dB, ( P < .001). The magnitude of LF ABG closure was over 1.5 times the magnitude of HF ABG closure ( P < .001). The gain in AC decreased with increasing frequency ( P < .001). Conclusion: Hearing improvement following stapedotomy is greater at low than high frequencies. Postoperative air bone gaps persist at 4 kHz. Further biomechanical and histopathologic work is necessary to localize postoperative high frequency conductive hearing deficits and improve stapedotomy hearing outcomes. Level of Evidence: 4, retrospective study.